Access to electricity for all and the role of decentralized solar power in sub-Saharan Africa. Issue 1 (1st January 2020) - Ulsrud, Kirsten
ABSTRACT: Several hundred million people in sub-Saharan Africa are at risk of being without access to electricity by 2030 despite the ongoing work aimed at achieving the United Nations' Sustainable Development Goal 7—sustainable energy for all. Based on qualitative interviews, quantitative surveys, observation, and participation in Kenya and Senegal between 2010 and 2018, the author aims to explain why the rate of progress is slower than intended. The findings highlight three strong hindrances: lack of affordability due to extreme poverty, mismatch between the village-level outreach of grid-based electricity systems and the geography of settlements, and lack of consideration given to gender inequality. The findings also provide new insights into the ways that decentralized small-scale solar power increasingly meets some of the shortcomings of centralized grids in addressing these three issues, even in rural areas where grids are already present. The author concludes that the ways in which village communities have combined the use of solar-powered energy with grid-supplied energy indicates the importance of the former and the need to intensify efforts to improve solar power delivery models and integrate them fully in energy sector strategies.